Why plaintiffs' attorneys use contingent and defense attorneys fixed fee contracts - Winand Emons; Claude Fluet (University of Bern, Department of Economics, 2013)
Victims want to collect damages from injurers. Cases differ with respect to the judgment. Attorneys observe the expected judgment, clients do not. Victims need an attorney to sue; defense attorneys reduce the probability that the plaintiff prevails. Plaintiffs' attorneys offer contingent fees providing incentives to proceed with strong and drop weak cases. By contrast, defense attorneys work for fixed fees under which they accept all cases. Since the defense commits to fight all cases, few victims sue in the first place. We thus explain the fact that in the US virtually all plaintiffs use contingency while defendants tend to rely exclusively on fixed fees.
Keywords: D82; K41; 330; litigation; contingent fees; fixed fees; expert services; Zivilprozess; Rechtsberufe; Honorar; Vergütungssystem; USA